India-Nigeria Collaboration: A South-South Perspectives (Global Journal of Human-Social Science, 2019)
Nigeria and India stand as Afro-Asian regional powers those emerge with the potentials and economic boosting. These make them play cardinal roles in the international political environment. Over several decades, these two nations have developed interesting ties concern economic, political and diplomatic spheres. Like many Afro-Asian nations, India and Nigeria were once victims of the British colonialism lasted until 15th August 1947 and 1st October 1960 respectively. This serves a lot in Afro-India capacity building. India and Nigeria are seen in different trends of engagement and passive attempts to create a reliable economy and sociopolitical success. That could be the point of reference to both Asian and African countries for many generations to come. Nigeria remains one of India's most important countries region-wide. For the last ten years or so, India is deeply investing largely in Africa's energy sector. Nigeria alone attracts a huge percentage of those investments. This project seeks to examine the changing nature of African foreign policy towards India particularly the paradoxical diplomatic relations between India and other African nations including Nigeria, and responses to the growing Afriphobia in India. It will also consider the potential uncertain in the future person-to-person contacts and transparency between the two sides.
Keywords: india and nigeria; global south; foreign direct investment; economic; security; diplomatic and trade ties